Romeo & Juliet - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. No fear Shakespeare graphic novels., 2008)
A retelling of Shakespeare's "Romeo and Juliet" in graphic novel format. Tells the tale of young lovers from rival families whose love destroys their families.